Hot springs in the Bombay Presidency : [records] - Purohit, S. R.; Kuṇṭe, Bha. Ga (Govt. of Maharashtra, Dept. of Archives, 1978)
Collection of letters and reports (1854-1860) written in connection with the hot springs in the former Bombay Presidency.